Evaluation of quality parameters in gluten-free bread formulated with breadfruit (Artocarpus altilis) flour - Clark, Elizabeth (Kansas State University, 2016)
Flour from the fruit of breadfruit trees (Artocarpus altilis) holds the potential to serve as an alternative to gluten-containing flour and may aid in alleviating food insecurity. This study assessed the effects breadfruit flour contributes to gluten-free bread quality. Breadfruit flour was included at a baker’s percentage (0, 20, 35, 50%) of a gluten-free flour blend, and was treated with various leavening agents (yeast, 15% baking powder, 20% baking powder) to create varying gluten-free bread formulas. Density and pH of each batter was assessed along with loaf density, yield, specific volume, pH, water activity, crust color (L*, a*, b*), crumb color (L*, a*, b*), and texture. Additionally, a consumer sensory study was performed to ascertain degree of liking of appearance, color, flavor, texture, aftertaste, likelihood to purchase, and overall acceptability. Significant differences (p < 0.05) were found in batter pH, loaf density, yield, specific volume, color (crust b*, crumb L*, a*, b*), pH, water activity, and texture among flour inclusion and leavening treatments. Consumer testing yielded significant differences (p < 0.05) between the control and a yeast leavened 20% breadfruit formula in appearance, color, flavor, aftertaste, likelihood to purchase, and overall acceptability. While most consumers rated the breadfruit treatment lower than the control, five celiac panelists rated it higher. Among all treatments, loaves produced from 20% breadfruit flour inclusion had significantly lower density, yield, hardness, adhesiveness, gumminess, chewiness, and crumb yellowness (b*), as well as higher specific volume, springiness, crust yellowness (b*) and darkness (L*), crumb darkness (L*), and magenta hue (a*) compared to other breadfruit flour inclusion levels. Similarly, loaves leavened with yeast had significantly lower batter pH, loaf pH, density, yield, hardness, chewiness, crust yellowness (a*), crumb darkness (L*), magenta hue (a*), and yellowness (b*) as well as higher loaf water activity, volume, springiness, and crust darkness (L*) compared to other breadfruit flour inclusion levels. These results indicate breadfruit flour can be used at ≤ 20% in gluten-free bread formulas to replace rice flour and has potential as a fiber supplement. Further research is needed to assess how breadfruit flour affects the quality of other gluten-free product formulas.
Keywords: Gluten-Free; Bread QualityBreadfruit Flour